Space Vector Modulation Technique for 3-Level NPC Converter with Constant Switching Frequency. (14th July 2016) - Ouerdani, Imen; Ben Abdelghani, Hafedh; Bennani Ben Abdelghani, Afef; Montesinos-Miracle, Daniel; Slama-Belkhodja, Ilhem
Abstract : This paper presents a simple Space Vector Modulation (SVM) methodology for a three-level NPC converter. Nearest three vectors (NTV) and corresponding duty cycles are deduced through simple generic mathematical expressions. Extra degrees of freedom of NPC converter are used to fully benefit from SVM advantages and to control the switching frequency. Simulation and experimental results are presented and discussed to validate the proposed methodology.